An Examination of Geomagnetic Induction in Submarine Cables - David H. Boteler; Shibaji Chakraborty; Xueling Shi; Michael D. Hartinger; Xuan Wang (Space Weather)
Abstract Submarine cables have experienced problems during extreme geomagnetic disturbances because of geomagnetically induced voltages adding or subtracting from the power feed to the repeaters. This is still a concern for modern fiber‐optic cables because they contain a copper conductor to carry power to the repeaters. This paper provides a new examination of geomagnetic induction in submarine cables and makes calculations of the voltages experienced by the TAT‐8 trans‐Atlantic submarine cable during the March 1989 magnetic storm. It is shown that the cable itself experiences an induced electromotive force (emf) and that induction in the ocean also leads to changes of potential of the land at each end of the cable. The process for calculating the electric fields induced in the sea and in the cable from knowledge of the seawater depth and conductivity and subsea conductivity is explained. The cable route is divided into 9 sections and the seafloor electric field is calculated for each section. These are combined to give the total induced emf in the cable. In addition, induction in the seawater and leakage of induced currents through the underlying resistive layers are modeled using a transmission line model of the ocean and underlying layers to determine the change in Earth potentials at the cable ends. The induced emf in the cable and the end potentials are then combined to give the total voltage change experienced by the cable power feed equipment. This gives results very close to those recorded on the TAT‐8 cable in March 1989.